Online Learning Through WhatsApp Group in Improving Learning Motivation in the Era and Post Pandemic COVID -19 - Samsul Susilawati; Triyo Supriyatno (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to find out the online learning process in the middle and post-pandemic Covid-19. This research employed one group pretest-posttest design. The subjects of the study were the fourth-semester students of the MPI Department of the State Islamic University of Maulana Malik Ibrahim Malang in the even semester of the academic year 2019/2020. The sample of this study was 30 students. Data obtained using a questionnaire. The data analysis technique used a paired T-test with an error rate of 5%. With online learning using WhatsApp shows that there is a correlation between the two variables of 0.776 it shows that there is a correlation between the pretest-posttest, the significance was 0.00 <0.05 then H0 was accepted. It further confirms that there is a significant increase in student learning outcomes before and after using WhatsApp. The results of the analysis and discussion can be concluded that there is an increase in online learning in the era and post-pandemic Covid-19 by using WhatsApp to increase learning motivation. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui proses pembelajaran online di tengah dan pasca pandemi Covid-19. Penelitian ini menggunakan one group pretest-posttest design. Subjek penelitian ini adalah mahasiswa semester empat Jurusan MPI Universitas Islam Negeri Maulana Malik Ibrahim Malang semester genap tahun ajaran 2019/2020. Sampel penelitian ini adalah 30 mahasiswa. Data diperoleh dengan menggunakan kuesioner. Teknik analisis data menggunakan paired T-test dengan tingkat kesalahan 5%. Pembelajaran online menggunakan whatsapp menunjukkan bahwa terdapat korelasi antara kedua variabel sebesar 0,776, hal ini menunjukkan bahwa terdapat korelasi antara pretest-posttest dengan signifikansi 0,00 <0,05 maka H0 diterima. Hasil ini semakin menegaskan bahwa ada peningkatan yang signifikan dalam hasil belajar siswa sebelum dan sesudah menggunakan WhatsApp. Hasil analisis dan pembahasan dapat disimpulkan bahwa terdapat peningkatan pembelajaran online di era dan pasca pandemi Covid-19 dengan menggunakan WhatsApp untuk meningkatkan motivasi belajar.